Subjective Well Being Pada Mahasiswi Tunanetra - Husin, Lauditta Soraya (Psikoislamedia: Jurnal Psikologi, 2020)
Abstact            Blind students with disabilities not only experience obstacles in the visual process but also have problems in the lecture process and social life including problems of accessibility, social relations, communication, difficulties in the lecture process and the views of the surrounding community. This affects the psychological condition of individuals, especially female students, this happens because women have genetic susceptibility, significant hormonal changes, a tendency to overthink things, and socio-cultural pressure. Alignment between the study process and self-acceptance with limited vision is the main goal that is continuously maintained and achieved by blind students, coupled with various pressures and problems in completing education, will be a challenge and pressure for students with visual impairments that can affect the subjective well-being of individuals ( Subjective Well Being). The purpose of this article is to determine the Subjective Well Being in blind female students and the factors that influence Subjective Well Being in blind female students. The method used is descriptive qualitative case study method. Participants in this study were three blind female students with data collection techniques through in-depth interviews and observations. The results showed that students with visual impairment have a Subjective Well Being in terms of dimensions of self-acceptance, life goals, self-growth, autonomy, environmental control, and positive relationships with others.Keywords: Subjective Well Being, Disabilities, Blind students